Evaluating the value of the timing of recurrence during blanking period after atrial fibrillation ablation. (3rd October 2022) - Lopes Da Cunha, G J; Bem, G; Durazzo, A; Matos, D; Rodrigues, G; Carmo, J; Carvalho, M S; Carmo, P; Santos, P G; Costa, F M; Cavaco, D; Morgado, F B; et al.
Abstract: Introduction: In the first weeks after atrial fibrillation (AF) ablation, the arrythmia may recur theoretically due to transient local inflammation and not due to treatment failure. This is defined as the blanking period, with a proposed duration of 3 months. Recently, this time period has been brought into question. The aim of this work was to evaluate the correlation between the timing of blanking recurrence and late AF recurrence. Methods: This was a single-centre retrospective study including patients without structural heart disease that underwent first AF ablation and were subsequently enrolled in the post ablation structured program between 2018 and 2021. Patients were excluded if they had <6 months follow-up. Appointment with ECG and Holter monitoring was performed at 1, 3, 6 and 12 months after ablation. Results: We included a total of 193 patients (56% male, mean age 63±12 years). Of these, 79% had paroxysmal AF and mean left atrial volume index was 58±18 mL/m 2 . During the 3-month blanking period, there were 39 (21%) recurrences, 18 (9%) of which in the first month. After blanking period, at 6 months, 25 (13%) patients had AF recurrence, 56% of which had already recurred during blanking period. AF recurrence in the 2nd and 3rd month of blanking increased the odd of recurrence at 6-month by more than 5-fold (odds ratio (OR) 8, 944; CI 95% 2, 817–28, 400, p<0.001 and OR 5, 591; 95% CI 1, 173–26, 651; p=0.031). On the other hand, recurrence of AF during the 1st month of blanking was not associated with increased chance of 6-month AF recurrence (OR 2, 095, 95% CI 0, 630–6, 964, p=0.227) (figure 1). There were no significant differences in clinical variables, including LA volume, between patients with 1-month recurrence and patients without recurrences. However, patients with AF recurrence in the 2nd and 3rd month of blanking had significantly increased LA volume. Conclusion: Our study suggests that patients with AF recurrence in the 2nd and 3rd month of blanking have structurally different atria and are at a significantly higher risk of post blanking AF recurrence, in contrast with patients with AF recurrence in the 1st month of blanking, thus questioning the appropriate duration of the blanking period. Funding Acknowledgement: Type of funding sources: None.